Cover Image. (23rd January 2020) - Ashokkumar, Chethan; Green, Michael; Soltys, Kyle; Michaels, Marian; Mazariegos, George; Reyes‐Mugica, Miguel; Higgs, Brandon W.; Spishock, Brianna; Zaccagnini, Madison; Sethi, Pradeep; Rzempoluch, Alexis; Kepler, Alexandra; et al.
Abstract : The cover image is based on the Original Article CD154‐expressing CMV‐specific T cells associate with freedom from DNAemia and may be protective in seronegative recipients after liver or intestine transplantation by Chethan Ashokkumar et al., https://doi.org/10.1111/petr.13601 .